The relationship between management’s commitment with job satisfaction according to shari’ah-based QMS (Ms1900:2014) at Malaysian higher education institution - Mohamed, Hasan Al Banna; Mohamad, Mohd Hamran; Basir, Siti Arni; Mohaiyadin, Norlaila Mazura; Saudi, Nur Surayya Mohd; Loong, Wong Wai (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Management’s commitment in an organisation plays an important role in ensuring the application of effective quality management system (QMS). This article explores the relationship between management’s commitment of an organisation that implements Shari’ah-based Quality Management System (MS1900:2014) with job satisfaction at Malaysian Higher Education Institution (HEI). The methodology of this study employed a qualitative design via a semi-structured interview conducted on selected respondents. The respondents consist of employees who are directly and actively involved with the implementation of MS1900 standard. The findings of this study show that management’s commitment has apparently influenced job satisfaction among employees at HEI. Therefore, the results of this study can serve as a guide to ensure that the implementation of quality management system based on Shari’ah standards (MS1900) can be applied effectively, blessed and rewarded by Allah SWT. © BEIESP.